Teachers’ evaluation of the project ”Little Physician” by the Polish Academy of Kids run at the Poznań University of Medical Sciences - Purandare, Barbara; Korzeniowska, Katarzyna Agnieszka; Stawczyk-Eder, Kamila; Pawlaczyk, Mariola (Journal of Medical Science, 2017)
Introduction. The project “Little Physician” has been run for over four years as a joint project of the Poznań University of Medical Sciences and the Polish Academy of Kids. It is an innovative undertaking in the international educational market, where young ‘scientists’ aged from 6 to 12 contribute to the classes and pursue their research interest in the broadly understood field of natural science. Aim. The aim of this research was to probe the opinions of the teachers participating in the “Little Physician” initiative. Material and Methods. The research was conducted on the population of 32 teachers. The applied technique was an interview based on an original questionnaire consisted of respondent`s particulars and 7 questions evaluating the usefulness, quality and thematic range of the classes, as well as the lecturers’ competencies and organisation of the classes. Results. The usefulness of the project was positively evaluated by all the interviewees (81% rated it as “very good”, 19% thought it was “good”). As many as 75% of the respondents decided that the thematic range of the lectures was “very good”. An even higher percentage assessed very positively the competencies of the adults giving lectures, the coordinators of the classes, the lecture halls and the manner in which classes were conducted. Conclusions. The project is very highly evaluated by the teachers supervising the participating children. The high assessment stems from the high competencies of the coordinators and lecturers participating in the classes, an accurate choice of issue or subjects discussed.
Keywords: schoolkids; teaching; medicine; innovation